Pelatihan manajemen keuangan dan online marketing pada UMKM Desa Sumur, Kecamatan Tamansari, Kabupaten Boyolali - Rofiuddin, Mohammad; Nabila, Rifda (Penamas: Journal of Community Service, 2024)
MSMEs must be able to compete in national and global markets, including MSMEs in Sumur Village, Boyolali Regency. The problem is that many MSMEs need better governance, especially in financial management and marketing patterns. Therefore, it is necessary to hold training activities that positively and appropriately impact the development of MSMEs in the future. The training activities include financial management training and online marketing training. The results of the community service show that the average level of understanding of financial management has increased before and after training. In addition, there has also been an increase in understanding among MSME actors regarding online marketing using e-commerce.